THE EFFECTIVENESS OF TELEMEDICINE ON THE IMPLEMENTATION MOTHER'S HYPNOBREASTFEEDING POSTPARTUM COVID-19 IN NORTH TAPANULI DISTRICT - Panggabean, Hetty W.A (Universitas Aisyah Pringsewu, 2023)
The aim of the research is to analyze and determine the effectiveness of the application of telemedicine to the implementation of hypnobreastfeeding in postpartum mothers during the Covid19 pandemic in North Tapanuli Regency in 2023. This type of quantitative research uses a cross sectional design at the Muara and Siborong-borong Community Health Centers March-September 2023. The sample consisted of 50 control group respondents and 50 experimental group respondents. Data processing uses univariate analysis and bivariate analysis with the chi-square statistical test. Result 1). In the Control group, through the pre-test, the Asymp value was obtained. Sig. (2-tailed) 0.3780.05 and 0.6580.05, so there is no relationship between knowledge and frequency and duration of breastfeeding. Asymp value. Sig. (2-tailed) 0.4460.05 and 0.5140.05, so there is no relationship between attitude and frequency and duration of breastfeeding 2). Experimental Group, through the pre-test, the Asymp value was obtained. Sig. (2-tailed) 0.9200.05 and 0.0420.05, there was no relationship between knowledge and frequency and duration of breastfeeding. Asymp. Sig. (2-tailed) 0.7420.05 and 0.0650.05, there is no relationship between attitude and frequency and duration of breastfeeding. Through the post test, the Asymp value was obtained. Sig.(2-tailed) 0.0020.05 and 0.0000.05 have a relationship between knowledge and the frequency and duration of breastfeeding. The conclusion is that there is a significant influence of Telemedicine on the Implementation of Hypnobreastfeeding in postpartum mothers during the Covid-19 pandemic in North Tapanuli Regency after receiving treatment.